Capital intelectual: um estudo de caso numa empresa de jornalismo - de Holanda, Lucyanno Moreira Cardoso; Silva Filho, Joel Freire; da Rocha, Ricardo Campos (Revista Gestão da Produção Operações e Sistemas, 2007)
The major productivity factor in an informational society – as the current one – is the people’s and enterprise’s capacity to generate, process and transform information and knowledge into economic assets. In order to acquire potentialized and continuous knowledge in the organizations, Karl Erik Sveiby emphasizes that it is necessary to have three structures: internal, external and the employees’ competences, in addition to establishing coherent strategies focused on the knowledge, not on information. Within this perspective, this paper aims at verifying the intangible assets of a journalism enterprise located at Campina Grande, Paraíba, Brazil, based on the model proposed by Sveiby (1998). The study is characterized as exploratory, with the use of qualitative techniques to data collection and analysis. The obtained results point out to the fact that, in the studied enterprise, there is not currently any systematic policy implemented that is specifically focused on intangible assets. Keywords: Intellectual capital; Knowledge management; Intangible assets; Service production.